2021
DOI: 10.1093/jpp/rgaa043
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles synthesized from Aspergillus terreus induces oxidative stress-mediated apoptosis through modulating apoptotic proteins in human cervical cancer HeLa cells

Abstract: Objectives This study was aimed to analyze the cytotoxicity of biogenic zinc oxide nanoparticles (ZnO NPs) in human cervical epithelial cancer HeLa. Methods The ZnO NPs was synthesized from the culture filtrated of Aspergillus terreus, and examined by UV-spectroscopy, X-ray diffraction (XRD), transmission electron microscope (TEM), energy-dispersive X-ray (EDX) and Fourier transform infrared (FTIR) analysis. The cytotoxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…However, no significant loss of MMP was reported for control (NTC). Chen et al [76] also supports our results where fungal-derived ZnONPs showed a loss of MMP in HeLa cells via ROS-triggered mitochondrial-pathwaymediated MMP reduction. Therefore, ZnONPs have been found to possess significant apoptosis inducing and anti-proliferative activity, which is enhanced due to the unique shape and smaller size of CE-UV-C-ZnONPs.…”
Section: Measurement Of Mitochondrial Membrane Potential (Mmp)supporting
confidence: 91%
See 1 more Smart Citation
“…However, no significant loss of MMP was reported for control (NTC). Chen et al [76] also supports our results where fungal-derived ZnONPs showed a loss of MMP in HeLa cells via ROS-triggered mitochondrial-pathwaymediated MMP reduction. Therefore, ZnONPs have been found to possess significant apoptosis inducing and anti-proliferative activity, which is enhanced due to the unique shape and smaller size of CE-UV-C-ZnONPs.…”
Section: Measurement Of Mitochondrial Membrane Potential (Mmp)supporting
confidence: 91%
“…Consequently, alternative, safe and effective anti-cancerous agents are required [80]. ZnONPs are one such nano-formulation known to exhibit cytotoxic effects against a number of cancer cells [76]. A possible mechanism for the anti-cancerous activity of ZnONPs is proposed.…”
Section: Caspase-3 Gene Expression and Caspase-3/7 Activitymentioning
confidence: 99%
“… 95 BNPs are one such nano-formulations known to exhibit cytotoxic effects against number of cancer cells. 96 The first step during NPs cytotoxicity against cancer cells is the internalization of NPs most probably via endocytosis pathway. Smaller sized NPs (approx.…”
Section: Resultsmentioning
confidence: 99%
“…GPx is an enzymatic free radical scavenger that could protect the body from ROS-induced damages. The accumulation of ROS and RNS after NM exposure was attributed to a reduced level and inactivation of GPx [ 57 , 58 ]. Similar to these cell studies, our meta-analysis identified a disturbance of GPx in NM-exposed workers.…”
Section: Discussionmentioning
confidence: 99%